The Moderating Effect of Perceived-Religiosity and Perceived-Health on Student Intention to Smoking Cessation - Arif Julianto Sri Nugroho; Agung Nugroho Jati; Abdul Haris; Anis Marjukah; DBP Setiyadi (Journal of Psychology and Instruction, 2024)
The consumer behavior of students at several private universities in Klaten to stop smoking with the issuance of the MUI fatwa on the prohibition of smoking and terrifying images warning of bad health effects on cigarette packaging was analyzed in this research by applying the TPB. The research objective is to test the independent variables of attitude, subjective norms and perceived behavior control which have a direct influence on student intention to smoke cessation. Primary data surveys are used as a quantitative research design. In this activity purposive sampling was used as a sampling technique. Data was collected through surveys and in-depth interviews with 300 students who had stopped smoking. The validity of the data was tested using item validity and reliability tests, goodness of fit tests and Structural Equation Model tests to test the influence of two moderating variables on the model simultaneously. The test results show that there is a direct influence of three independent variables on students' motivation to stop smoking. One moderating variable perceived- health is able to strengthen the influence of the independent variable on student intention to smoke cessation, while one moderating variable perceived-religiosity is not able to strengthen the influence of the independent variable on the student intention to smoke cessation variable.